Pengaruh Leadership, Lingkungan Kerja dan Karakteristik Pekerjaan Terhadap Kepuasan Kerja dengan Budaya Organisasi Sebagai Variabel Mediasi - Krismanita, Nazia; Chalimah, Chalimah (DAS Institute, 2025)
One of the main issues is leadership, which has not yet fully motivated and guided employees effectively, especially in facing production demands and market changes. This study aims to determine and analyze how leadership, work environment, and job characteristics affect employee job satisfaction through organizational culture as an mediating variable. This type of research is correlational, with data collection using questionnaires. The population of this study consists of all employees at the Goyor Sarung factory owned by Bapak Gampang in Pemalang. The sample of this study is 112 people using a saturated sampling technique. This research uses the SPSS version 25 data processing tool. The results show that leadership has a significant positive effect on job satisfaction. Job characteristics have a significant positive effect on job satisfaction. Organizational culture has a significant positive effect on job satisfaction. Meanwhile, the work environment has a negative and insignificant effect on job satisfaction. The leadership variable has a significant effect on employee job satisfaction through organizational culture as an mediating variable. The work environment has a significant effect on employee job satisfaction through organizational culture as an mediating variable. Job characteristics have a significant effect on employee job satisfaction through organizational culture as an mediating variable.